Automação de sistema de motores de um forno elétrico para deposição de filmes finos pela técnica de spray-pirólise - Oliveira, Fernando Weslley Silva de (2020)
Automation aims at the safety of people, the quality of products, the speed of production and the reduction of costs, thus improving the complex objectives of industries and services. Automated processes are growing in the industry and their use with renewable energies is on the rise, maximizing the potential for converting sources into secondary energy and electricity. This work proposed to automate a heating chamber and electric oven to obtain a conductive surface through a transparent substrate through the implementation of computational codes in the Arduino IDE and the use of languages such as C, C ++ and Python to control stepper motors, thermocouples, drives and shields, and performing temperature detection and reading by means of sensors and actuators. Mechanical analysis was performed to visualize the gears and positioning of the components; electrical analysis with diagrams and assemblies of the stepper motor with the arduino; and computational analysis for the development of the algorithms. Codes were obtained that controlled three stepper motors; an M1 engine responsible for opening and closing the electric oven lid with codes in C, C ++ and Python; an M2 motor responsible for the movement on the x axis inside and at the top of the chamber; and an M3 motor for angular movement of the airbrush, so that, using the spray pyrolysis technique, deposit the liquid on the transparent substrate. There was the implementation of a code for the detection and reading of the temperature at two different points, using three functions for reading the SPI serial data protocol, another for reading from the MAX6675 module and one implementing a SPI for reading and storing data on a card SD. It was possible an analysis and practical understanding of the best configurations of all the main construction elements that make up an electric resistance furnace. The code showed good communication between the two stepper motors. The temperature detection step was successfully completed, capturing temperatures and saving data. The use of other programming languages in the electric oven cover circuit proved to be a strong tool as a communication intermediary between the user and the embedded system. The study proved to be feasible for implementation in the thermal chamber and oven and to reference that automated processes are carried out in addition to contributing scientifically to future energy system optimization projects.